Prevalence of Edentulousness among Patient visiting a Tertiary Care Centre - Pandey, Anisha; Basnet, Srijan Singh; Neupane, Ajay (Nepal Journal of Health Sciences, 2024)
Introduction: Absence of teeth i.e., edentulism is a common oral health issue worldwide and is an under evaluated disability. It is a preventable oral disability which brings major impact on overall health of individuals affecting the function, aesthetics, comfort and psychology. So, it should be identified and awareness for its management should be done so as to improve the quality of life of an individual. Objective: The purpose of this study was to collect baseline data on edentulism in the Nepalese population so that community-level awareness and educational programs could explain the importance of replacement lost teeth with prosthesis. Methods: The study was conducted in the College of Medical Sciences in the department of Oral medicine and Radiology and in the department of Prosthodontics from the patient visiting in these OPD for five months duration. Data were recorded in proforma and classified as complete / partial edentulous and further classified into Kennedy’s classification. The data were recorded and analyzed in SPSS 20. Result: Out of 301 patients, 24 (8%) had total edentulism, while 277 (92% had partial edentulism). Of the partially edentulous individuals, 90 showed just maxillary edentulism, 148 showed only mandibular edentulism, and 39 showed both maxillary and mandibular edentulism. Conclusion: Females were more likely than males to exhibit partial edentulism. Females showed more Kennedy’s Class III classification than males. Both had equal complete edentulism. The mandibular arch showed more partial edentulism than the maxillary arch.